3D printed receptacle with diffuser membrane for manipulating pressurized air and water. (April 2021) - Pálfy, Tamás Gábor; Török, Luca; Kalicz, Péter; Gribovszki, Zoltán
Graphical abstract: Highlights: An FDM-3D printed multi-feature laboratory receptacle is reported on. Water tightness and permeability in a single 3D printed body is detailed. Slicing software and gcode post-processing settings are quantified. Tests of the diffuser membrane in the object are evaluated. Hardware specifications and costs are reported. Abstract: Water research is one of many fields where fused filament fabrication 3D printing offers the freedom of customization and the inclusion of commercial components. We present our 330 mL 3D printed laboratory receptacle that has been customized to control pressurized air and liquid in one body. During our tests, water has been stored without loss, and batches were frozen whilst circulating and diffusing air through the liquid. The printing has been optimized with the slicer software and gcode editing, letting the fused filament 3D printer to build a diffuser membrane surrounded by air-tight walls. Detailed construction instructions are given, including piping and control board for operation. According to the functionality of the receptacle and the aeration system, the solutions have been found durable and low-cost. Disadvantages are the time invested in creating customized code, and certain limitations of the membrane itself.